Labelling as reference Centre of GRACE (Groupe francophone de Réhabilitation Améliorée après ChirurgiE) for colorectal surgery: its impact on the implementation of enhanced recovery programme at the University Hospital of Liège. Issue 5 (3rd September 2018) - Daenen, Coralie; Coimbra, Carla; Hans, Grégory; Joris, Jean
Abstract: Background: Enhanced recovery programme (ERP) has been used in our hospital since 2005 for selected colorectal surgeries. Since October 2015, after labelling as GRACE reference centre, we included all patients scheduled for elective colorectal surgery in this programme. We assessed the impact of our labelling on the implementation of ERP. Methods: Results of our first 100 patients entered in the GRACE database were analyzed: length of stay, complications, readmission, adherence to the protocol. These results are compared to those of the last 100 patients undergoing colorectal surgery before our labelling. Results: Patients' characteristics in both groups were similar. The complications rate was similar in both groups. The global length of hospital stay was 4 [5] days vs. 8.5 [8] (median [IQR]), respectively after and before labelling; p  < .001. The duration of hospitalization for the different subgroups (age, surgical approach, types of surgery) were significantly shorter after our labelling (respectively: p  < .001, p < .01, and p  < .05). Conclusions: Our results demonstrate that labelling as reference centre increases the efficiency of the implementation of ERP. The fact that all subgroups of patients benefit from ERP must encourage inclusion of all patients undergoing elective colorectal surgery in ERP.